A eukaryotic gene encoding an endonuclease that specifically repairs DNA damaged by ultraviolet light. - Yajima, H (1995)
Many eukaryotic organisms, including humans, remove ultraviolet (UV) damage from their genomes by the nucleotide excision repair pathway, which requires more than 10 separate protein factors. However, no nucleotide excision repair pathway has been found in the filamentous fungus Neurospora crassa. We have isolated a new eukaryotic DNA repair gene from N.crassa by its ability to complement UV-sensitive Escherichia coli cells. The gene is altered in a N.crassa mus-18 mutant and responsible for the exclusive sensitivity to UV of the mutant. Introduction of the wild-type mus-18 gene complements not only the mus-18 DNA repair defect of N.crassa, but also confers UV-resistance on various DNA repair-deficient mutants of Saccharomyces cerevisiae and a human xeroderma pigmentosum cell line. The cDNA encodes a protein of 74 kDa with no sequence similarity to other known repair enzymes. Recombinant mus-18 protein was purified from E.coli and found to be an endonuclease for UV-irradiated DNA. Both cyclobutane pyrimidine dimers and (6-4)photoproducts are cleaved at the sites immediately 5' to the damaged dipyrimidines in a magnesium-dependent, ATP-independent reaction. This mechanism, requiring a single polypeptide designated UV-induced dimer endonuclease for incision, is a substitute for the role of nucleotide excision repair of UV damage in N.crassa.